DO OUR NURSES HAVE SUFFICIENT KNOWLEDGE OF PAIN? A DESCRIPTIVE STUDY IN HAJI ADAM MALIK HOSPITAL MEDAN- INDONESIA - Ikhsanuddin Ahmad Harahap (UNEJ e-Proceeding)
Background: Pain treatments are closely related to pain assessment. Pain is probably one of the most common clinical phenomenon faced by nurses. Therefore, nurses are required to have adequate knowledge, skills and attitudes about pain, pain assessment and pain management. The objective of this descriptive explorative study was to identify the nurse's knowledge of pain, Methods: The samples were 33 nurses selected using convenience sampling method from medical surgical wards in selected hospital in Medan. Data were collected by using demography questionnaires and pain knowledge question sheet 30 items, Results: Subjects knowledge of pain ranged from 5 to 20 with average knowledge 11,33 (SD=3,33). Based on pain knowledge categories, more than half subjects (63,7%) were in moderate level, low level (33,3%), and only 3,0% in high level. Furthermore, based on subscales of pain knowledge, it was found moderate level of pain categories (M=3,82;SD=1,33) and pain mechanism’s subscales (M=2,03;SD=1,05). However, this study also found that pain definition (M=0,97;SD=0,98), pain behaviours (M=1,52;SD=1,09), and pain assessment’s subscales (M=3,00;SD=1,54) were in low level. In order to improve nurses knowledge of pain as well as the accuracy of pain assessment assessed by nurses, therefore nurses knowledge of pain need to be updated, Conclusions: this study found that nurses knowledge of pain was sufficient in moderate level, however need to be improved especially in three areas of knowledge including: pain definition, pain behaviours, and pain assessment. Keywords: pain, knowledge, nurse